2015
DOI: 10.18632/oncotarget.6659
|View full text |Cite
|
Sign up to set email alerts
|

Replication stress induced site-specific phosphorylation targets WRN to the ubiquitin-proteasome pathway

Abstract: Faithful and complete genome replication in human cells is essential for preventing the accumulation of cancer-promoting mutations. WRN, the protein defective in Werner syndrome, plays critical roles in preventing replication stress, chromosome instability, and tumorigenesis. Herein, we report that ATR-mediated WRN phosphorylation is needed for DNA replication and repair upon replication stress. A serine residue, S1141, in WRN is phosphorylated in vivo by the ATR kinase in response to replication stress. ATR-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 68 publications
2
30
0
Order By: Relevance
“…Hence, our data cannot discriminate between direct vs. indirect effect of ATM inhibition on WRN S1141 phosphorylation in cellulo. Our previous in vitro experiments revealed that S1141 of WRN is targeted by ATM but not ATR (Ammazzalorso et al, 2010), however, another study has demonstrated that it is phosphorylated by ATR in cellulo, at least during extended period of recovery after CPT (Su et al, 2015). The resection-defective phenotype of the S1141D-WRN mutant, the elevated levels of pS1141-WRN during recovery from CPT treatment would support the possibility that S1141 of WRN is targeted by ATR also in our conditions.…”
Section: Phosphorylation Of Wrn At S1141 and Regulation Of Long-rangesupporting
confidence: 55%
See 1 more Smart Citation
“…Hence, our data cannot discriminate between direct vs. indirect effect of ATM inhibition on WRN S1141 phosphorylation in cellulo. Our previous in vitro experiments revealed that S1141 of WRN is targeted by ATM but not ATR (Ammazzalorso et al, 2010), however, another study has demonstrated that it is phosphorylated by ATR in cellulo, at least during extended period of recovery after CPT (Su et al, 2015). The resection-defective phenotype of the S1141D-WRN mutant, the elevated levels of pS1141-WRN during recovery from CPT treatment would support the possibility that S1141 of WRN is targeted by ATR also in our conditions.…”
Section: Phosphorylation Of Wrn At S1141 and Regulation Of Long-rangesupporting
confidence: 55%
“…Of note, the K577M-WRN mutant shows high basal levels of pS1141. Phosphorylation at S1141 has been also linked to degradation of WRN during extended recovery from replication-dependent DSBs (Su et al, 2015). Thus, elevated basal levels of pS1141 in the K577M-WRN could correlate with the need to degrade the mutant protein.…”
Section: Phosphorylation Of Wrn At S1141 and Regulation Of Long-rangementioning
confidence: 99%
“…The results suggest that the activation of the DDR by E1 (as we have and others have demonstrated previously) stimulates SIRT1 to deacetylate WRN. This deacetylation contributes to the destabilization of the WRN protein when the DDR is activated and previous studies have demonstrated that activation of the DDR results in promotion of WRN degradation (76). Acetylation of WRN prevents ubiquitination and therefore inhibits its degradation via the proteasome (57), therefore depletion of SIRT1 protects the E1 mediated degradation of FLAG-WRN.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of MG132 partially restores WRN expression levels in the presence of E1 (Figs. 5a and 5b) suggesting that activation of the DDR by E1 promotes degradation of WRN via the proteasome, similarly to exogenous agents that activate the DDR (76). The E2 protein was stabilized by the addition of MG132 and we have demonstrated previously that the turnover of this protein is regulated via the proteasome (77).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation